2017
DOI: 10.1007/s11695-017-3018-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Loss on Acoustic Parameters After Bariatric Surgery

Abstract: Obese individuals with post-surgery weight loss may present neck circumference, fundamental frequency, and maximum phonation time values closer to the mean values of normal weight individuals. In this study, weight loss was sufficient to adjust the acoustic parameter measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, our findings also suggested a small increase in MPT after the surgery, possibly requiring a longer postoperative period or even greater weight loss for the MPT to improve significantly. A previous study showed that it was possible to see improvements in MPT eight months after the surgery [15]. In our study, patients of group D showed an increase in the MPT of the vowel /A/ after the surgery and in group B an almost significant positive relation between percentage of weight loss and MPT for /A/ and /I/.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, our findings also suggested a small increase in MPT after the surgery, possibly requiring a longer postoperative period or even greater weight loss for the MPT to improve significantly. A previous study showed that it was possible to see improvements in MPT eight months after the surgery [15]. In our study, patients of group D showed an increase in the MPT of the vowel /A/ after the surgery and in group B an almost significant positive relation between percentage of weight loss and MPT for /A/ and /I/.…”
Section: Discussionsupporting
confidence: 62%
“…ese investigations included a small number of individuals, less than ten, but use adequate methodology to evaluate voice. On the other hand, two studies reported an increase in MPT and in fundamental frequency eight months after surgery [11,15]. ese investigations included a larger number of obese patients (more than twenty), but of women only, which differs from our study group.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although these findings are interesting, the studies suffer generally from a sample size that is either not sufficiently large or sufficiently diverse to generalize across the entire human population. For example, the study by Pawelec et al (2020) includes only young men, aged 18–33 from two cities in Poland, showing a lack of diversity; that by Evans et al (2006) includes only heterosexual, English-speaking men, again showing a lack of diversity; and that by de Souza et al (2018) involved only 25 morbidly obese participants. Additionally, while there may be average differences in voice types affected by certain biological factors, there is a lot of individual variability, and it should be more important to find a person’s healthy vocal Fach than to make them conform to what the average “should” be.…”
Section: Introductionmentioning
confidence: 99%